Fixed Points Results in G-Metric Spaces - Salwa Salman Abed; Anaam Neamah Faraj (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2019)
In this paper, the concept of contraction mapping on a -metric space is extended with a consideration on local contraction.  As a result, two fixed point theorems were proved for contraction on a closed ball in a complete -metric space.